Loss of prolyl-hydroxylase 1 protects against biliary fibrosis via attenuated activation of hepatic stellate cells - Strowitzki, Moritz; Kirchberg, Johanna; Tuffs, Christopher; Schiedeck, Maximilian Georg; Ritter, Alina; Biller, Marvin; Harnoß, Jonathan M.; Lasitschka, Felix; Schmidt, Thomas; Radhakrishnan, Praveen; Ulrich, Alexis; Schneider, Martin (The American journal of pathology, 2018)
Liver fibrosis, eventually progressing to cirrhosis necessitating liver transplantation, poses a significant clinical problem. Oxygen shortage (hypoxia) and hypoxia-inducible transcription factors (HIFs) have been acknowledged as important drivers of liver fibrosis. The significance of oxygen-sensing HIF prolyl-hydroxylase (PHD) enzymes in this context has, however, remained elusive. In this study, we demonstrate that loss of PHD1 (PHD1−/−) attenuates the development of liver fibrosis in mice subjected to chronic bile duct injury, induced by 3,5-diethoxycarbonyl-1,4-dihydrocollidine. This effect was accompanied with reduced recruitment of inflammatory leukocytes and attenuated occurrence of profibrotic myofibroblasts in PHD1−/− livers. Further analyses focused on the significance of PHD1 in the activation of hepatic stellate cells (HSCs), which represent the driving force in liver fibrosis. Primary HSCs isolated from PHD1−/− mice displayed significantly attenuated myofibroblast differentiation and profibrogenic properties compared with HSCs isolated from wild-type mice. Consistently, the expression of various profibrogenic and promitogenic factors was reduced in PHD1−/− HSCs, without alterations in HIF-1α protein levels. Of importance, PHD1 protein was expressed in HSCs within human livers, and PHD1 transcript expression was significantly increased with disease severity in hepatic tissue from patients with liver fibrosis. Collectively, these findings indicate that PHD1 deficiency protects against liver fibrosis and that these effects are partly due to attenuated activation of HSCs. PHD1 may represent a therapeutic target to alleviate liver fibrosis.
Gesehen am 20.04.2020